MENEJEMEN PENANGANAN PERILAKU HIPERAKTIF ANAK USIA DINI DI BA ‘AISYIYAH WATUBELAH - Novita, Fia; Munawaroh, Hidayatu; Muntaqo, Rifqi (Universitas Nahdlatul Ulama Al Ghazali Cilacap, 2021)
This study aimed to describe: (1) the behavior of hyperactive children in BA ‘Aisyiyah Watubelah, (2) factors that cause child hyperactivity in BA ‘Aisyiyah Watubelah, (3) countermeasures for hyperactive children in the BA ‘Aisyiyah Watubelah. This research is qualitative. Subjects in this study were principals, teachers who teach in class, hyperactive children, and the elderly. Data collection techniques used were observation, interview, documentation, and field notes. The results showed that the behavior of hyperactive children Ilham as, among others: often interfere another friend, did not want to be regulated, often leave their seats during the learning, and often do not complete the task. Meanwhile, Azka's behavior as hyperactive children, among others: has a high temper, often hurt others, often leaves seat of learning time, and spoiled. These behaviors are caused by environmental factors or a family home. Through interviews with the parents of the child, that parents often give Azka physical violence or words when guiding children, while parents often indulge Ilham and the wishes of children. The behavior of hyperactive children is caused by these factors can be overcome with some effort, among others: given a reprimand when they made mistakes, impose sanctions according to ability of children, do not need to provide when guiding a hyperactive child abuse.